Pathogenic germline variants in SMARCA4 and further cancer predisposition genes in early onset ovarian cancer - Natalie Herold; Johanna Schmolling; Corinna Ernst; Beyhan Ataseven; Britta Blümcke; Birgid Schömig‐Markiefka; Sebastian Heikaus; Uwe‐Jochen Göhring; Christoph Engel; Björn Lampe; Kerstin Rhiem; Philipp Harter; et al. (Cancer Medicine, 2023)
To assess the role of germline pathogenic variants (PVs) in SMARCA4 and further established ovarian cancer (OC) predisposition genes in early onset OC, we investigated a clinical cohort of 206 unrelated OC index patients with an age at diagnosis of OC ≤40 years using an extended panel of 24 (candidate) cancer predisposition genes. PVs in established OC predisposition genes were most frequent in patients with high grade serous OC (21/62, 33.9%), comparatively rare in patients with epithelial OC other than high grade serous (5/74, 6.8%) or borderline ovarian tumours (2/39, 5.1%) and absent in mucinous OC (0/27). We demonstrate that germline PVs in SMARCA4 unlikely predispose for early onset OC other than SCCOHT.